2019
DOI: 10.1002/slct.201900533
|View full text |Cite
|
Sign up to set email alerts
|

Fe2O3 Nanoparticles Modified 2D N‐Doped Porous Graphene‐like Carbon as an Efficient and Robust Electrocatalyst for Oxygen Reduction Reaction

Abstract: As the high expense and poor stability of Pt-based catalysts have severely limited the commercial applications of cathodic catalysts in fuel cells, the steps towards developing low-cost and stable catalysts for oxygen reduction reaction (ORR) have never stopped. In this work, we designed a Fe 2 O 3 nanoparticles decorated 2D N-doped porous graphene-like carbon material (Fe(1.0)-N/C-800) from the one-step pyrolysis of low-cost and abundant substrates (β-cyclodextrin, urea and FeCl 3 ) under N 2 atmosphere. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The peak at 708.3 eV could be consistent with the FeÀ Nx species [9,36] . The pair of Fe 2p 3/2 (∼ 711.2 eV)/Fe 2p 1/2 (∼ 724.4 eV) and Fe 2p 3/2 (∼ 711.2 eV)/Fe 2p 1/2 (∼ 724.4 eV) were ascribed to Fe 2 + and Fe 3 + [23,[37][38][39] , respectively. Finally, XPS survey spectra (Figure5d and Table S2) of Fe-CNTs/ NC revealed that the main elements are iron, nitrogen, carbon, oxygen and little negligible zinc.…”
Section: Resultsmentioning
confidence: 97%
“…The peak at 708.3 eV could be consistent with the FeÀ Nx species [9,36] . The pair of Fe 2p 3/2 (∼ 711.2 eV)/Fe 2p 1/2 (∼ 724.4 eV) and Fe 2p 3/2 (∼ 711.2 eV)/Fe 2p 1/2 (∼ 724.4 eV) were ascribed to Fe 2 + and Fe 3 + [23,[37][38][39] , respectively. Finally, XPS survey spectra (Figure5d and Table S2) of Fe-CNTs/ NC revealed that the main elements are iron, nitrogen, carbon, oxygen and little negligible zinc.…”
Section: Resultsmentioning
confidence: 97%
“…18,19 2D N-doped porous graphene-like carbon material-encapsulated Fe 2 O 3 nanoparticles were prepared by β-CD, and the electron transfer to O 2 was enhanced, boosting the oxygen reduction reaction process, which was contributed to the graphene high performance for both storage and transfer of electrons. 20,21 In this work, Cu 0 @CuO x -encapsulated nitrogen-doped graphitized carbon (Cu 0 @CuO x -NC) was prepared by the one-step pyrolysis of low-cost and abundant substrates, β-CD, urea, and CuCl…”
Section: Introductionmentioning
confidence: 99%
“…The efficient adsorption ability of β-CD to some appropriate molecules is attributed to its hydrophilic group hydroxyl group, which readily forms coordination complexes with excess metals. , Moreover, molecules of appropriate size and shape can enter the cavity to form inclusion compounds through host–guest interactions . For example, β-CD has been used to complex iron and copper oxides by Fe­(Cu)–O–C, enhancing M n + /M ( n + m )+ cycling and the interaction of organic pollutants with the catalysts, causing higher Fenton-like efficiency. , 2D N-doped porous graphene-like carbon material-encapsulated Fe 2 O 3 nanoparticles were prepared by β-CD, and the electron transfer to O 2 was enhanced, boosting the oxygen reduction reaction process, which was contributed to the graphene high performance for both storage and transfer of electrons. , …”
Section: Introductionmentioning
confidence: 99%
“…Modified carbon materials, such as carbon nanotubes, graphene and mesoporous carbons with unique physical and chemical properties after doping with heteroatoms, have drawn intensive interest for their excellent performances in ORR catalysis [10][11][12][13]. Among the generally doped foreign atoms, nitrogen could not only alter the electronic property and crystal structure of catalysts, but also prominently transform the chemical stability, surface polarity and electron-donor properties of the carbon materials, which effectively promoted the ORR catalysis [14].…”
Section: Introductionmentioning
confidence: 99%